1948
DOI: 10.1111/j.1365-2494.1948.tb00851.x
|View full text |Cite
|
Sign up to set email alerts
|

Underground Development and Reserves of Grasses a Review

Abstract: The roots of plants are the least known, least understood and least appreciated part of the plant."-^\Veaver and Bruner (125).The underground parts of perennial grasses serve not only as anchorage and organs of absorption of water and nutrients, but also for the storage of reserves, and there exist significant interrelations between herbage growth and underground development. The aim of modem grassland husbandry is to produce and maintain maximum yields of high qiiality fodder. To achieve this, an imderstandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0
1

Year Published

1949
1949
1998
1998

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 60 publications
(76 reference statements)
1
35
0
1
Order By: Relevance
“…It is suggested that the amount of shoot remaining for supplying stored food or for photosynthesis is the important factor (Harrison & Hodgson 1939;Lovvorn 1945;Julander 1945;Weinmann 1948).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that the amount of shoot remaining for supplying stored food or for photosynthesis is the important factor (Harrison & Hodgson 1939;Lovvorn 1945;Julander 1945;Weinmann 1948).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these recent papers are by BENEDICT and BROWN (2), PHILLIPS and SMITH (9), MCILVANIE (8), WEIN-MANN and REINHOLD (18), and WEINMANN (13,14,15,16). A review by Weinmann covers the general subject of reserves in grasses (17).…”
mentioning
confidence: 99%
“…Most reports deal with the effects of grazing and cutting on carbohydrates in below ground parts (McCarty, 1935;Sullivan & Sprague, 1949, 1953Weinmann, 1948;Baker, 1957;Nelson & Smith, 1968;Sheard, 1973;Lytle & Hull, 1980). In Sheard's paper, translocation of carbohydrates measured with ^^C is discussed.…”
Section: Introductionmentioning
confidence: 99%